Shear lag analysis of placed structures by adaptive finite element method - Wu, Gao Jun. (2008)
In this study, shear lag problem of plated structures with arbitrary dimensional geometry is solved by the adaptive finite element analysis procedure provided by the commercial software LUSAS. The adaptive finite element analysis procedure makes it possible to get results with predetermined accuracy with a minimum amount of computational cost.